Can Exposure to Volatile Anesthetics Be a Tipping Point for AD Susceptible Populations? - Ingrid R Niesman (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2017)
The relationship between surgery induced Postoperative Cognitive Dysfunction (POCD) and the development of Alzheimer's disease (AD) later has been a debatable question. Volatile anesthetics represent a potential environmental factor that can change the CNS both acutely and long-term. By interacting with membrane cholesterol to alter signaling in neurons or alter the normally quiescent microglial phenotype, volatile anesthetics are implicated in the development of POCD. The tipping point for triggering AD cyclic pathology may rest with individual AD genetic risk factors combined with the known molecular consequences of anesthetic exposure. This review covers genome wide association studies (GWAS) identified AD risk factors, actions of volatile anesthetics in the development of AD phenotypes and presents some newly discovered pre or post-anesthetic POCD attenuating therapies.